A Profile of Acute Care in an Aging America: Snowball Sample Identification and Characterization of United States Geriatric Emergency Departments in 2013. (March 2014) - Hogan, Teresita M.; Olade, Tolulope Oyeyemi; Carpenter, Christopher R.; Gerson, Lowell
Abstract Background The aging of America poses a challenge to emergency departments (EDs). Studies show that elderly patients have poor outcomes despite increased testing, prolonged periods of observation, and higher admission rates. In response, emergency medicine (EM) leaders have implemented strategies for improved ED elder care, enhancing expertise, equipment, policies, and protocols. One example is the development of geriatric EDs gaining in popularity nationwide. To the authors' knowledge, this is the first research to systematically identify and qualitatively characterize the existence, locations, and features of geriatric EDs across the United States. Objectives The primary objective was to determine the number, distribution, and characteristics of geriatric EDs in the United States in 2013. Methods This was a survey with potential respondents identified via a snowball sampling of known geriatric EDs, EM professional organizations' geriatric interest groups, and a structured search of the Internet using multiple search engines. Sites were contacted by telephone, and those confirming geriatric EDs presence received the survey via e‐mail. Category questions included date of opening, location, volumes, staffing, physical plant changes, screening tools, policies, and protocols. Categories were reported based on general interest to those seeking to understand components of a geriatric ED. Results Thirty‐six hospitals confirmed geriatric ED existence and received surveys. Thirty (83%) responded to the survey and confirmed presence or plans for geriatric EDs: 24 (80%) had existing geriatric EDs, and six (20%) were planning to open geriatric EDs by 2014. The majority of geriatric EDs are located in the Midwest (46%) and Northeast (30%) regions of the United States. Eighty percent serve from 5, 000 to 20, 000 elder patients annually. Seventy percent of geriatric EDs are attached to the main ED, and 66% have from one to 10 geriatric beds. Physical plant changes include modifications to beds (96%), lighting (90%), flooring (83%), visual aids (73%), and sound level (70%). Seventy‐seven percent have staff overlapping with the nongeriatric portion of their ED, and 80% require geriatric staff didactics. Sixty‐seven percent of geriatric EDs report discharge planning for geriatric ED patients, and 90% of geriatric EDs had direct follow‐up through patient callbacks. Conclusions The snowball sample identification of U.S. geriatric EDs resulted in 30 confirmed respondents. There is significant variation in the components constituting a geriatric ED. The United States should consider external validation of self‐identified geriatric EDs to standardize the quality and type of care patients can expect from an institution with an identified geriatric ED.